2021
DOI: 10.20998/2522-9052.2021.4.07
|View full text |Cite
|
Sign up to set email alerts
|

Development and research of the parameters control system of the artificial ecosystem environment by the fuzzy-logic system

Abstract: The paper considers the solution of scientific and practical problem of development and research of control system of parameters of environment of artificial ecosystem, creation of structural and basic electric scheme of system, drawing up of algorithm of its work. The study consists of statistical processing of the results of direct repeated measurements of soluble oxygen level, pH, temperature in the aquarium of the artificial ecosystem, analysis of errors and total standard uncertainty of measurement result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Щоб отримати якісну продукцію, необхідно розробляти автоматизовані інформаційновимірювальні системи контролю найбільш важливих для якості параметрів технологічного процесу виготовлення майонезу, що здатні забезпечити максимальну точність вимірювань фізичних величин, завдяки використанню вдосконаленої елементної бази. У роботах [6][7][8] На підставі розглянутих датчиків температури встановлено, що для здійснення вимірювань температури до + 100 0 С з високою точністю ± 0,5 0 С, яке необхідно проводити при виробництві майонезу, найкраще підходить датчик температури моделі 1-3ФТ фірми ЧАТ «ТЭРА» Україна [10] (рис. 3).…”
Section: вступunclassified
“…Щоб отримати якісну продукцію, необхідно розробляти автоматизовані інформаційновимірювальні системи контролю найбільш важливих для якості параметрів технологічного процесу виготовлення майонезу, що здатні забезпечити максимальну точність вимірювань фізичних величин, завдяки використанню вдосконаленої елементної бази. У роботах [6][7][8] На підставі розглянутих датчиків температури встановлено, що для здійснення вимірювань температури до + 100 0 С з високою точністю ± 0,5 0 С, яке необхідно проводити при виробництві майонезу, найкраще підходить датчик температури моделі 1-3ФТ фірми ЧАТ «ТЭРА» Україна [10] (рис. 3).…”
Section: вступunclassified
“…It is shown that the construction of a suitable classifier could significantly improve the efficiency of further image processing operations: localization, recognition, search, and tracking of covered by fires and forecasting the future occurrence of this natural disaster with further consequences was not considered. Paper [20] considers the solution to the problem of developing and researching a system for controlling the parameters of the environment of an artificial ecosystem and the use of fuzzy logic to establish relationships between parameters. The issue of controlling and monitoring the microclimate of the entire ecosystem remains unresolved.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Thus, our review of literary sources [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] revealed that they lack analysis based on a mathematical apparatus that detects the influence of harmful factors, and it is not specified where and how the information obtained and processed is stored. The issues of efficiency in determining forest areas that were affected by forest fires, with their further classification, assessment of burned areas, and analysis of relationships between parameters that negatively affect the tree stand remain unsolved.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%